Discovery of four new species of Trichrysis Lichtenstein, cyanea species group (Hymenoptera, Chrysididae) from Vietnam - Wiśniowski, Bogdan; Lien, Nguyen Thi Phuong; Cuong, Nguyen Quang (Zootaxa, 2020)
Four species of the genus Trichrysis Lichtenstein, 1876 are described from Vietnam as new for science: T. aliciae Wiśniowski, sp. nov., T. chamchuensis Wiśniowski & Nguyen, sp. nov., T. kylan Wiśniowski & Cuong, sp. nov., and T. raymundi Wiśniowski, sp. nov. The species belong to the T. cyanea species group.